Vice-Chancellor opens games by Malaysian students - Haryani, Abdullah
Universiti Malaysia Pahang (UMP) Vice-Chancellor, Dato’ Dr. Daing Nasir Ibrahim officially opened the Midwest Games International (MWGi) organised by the Malaysian Embassy in Chicago (EMC) and Western Michigan University (WMU) Malaysian Student Association (MASA) at Kalamazoo, Michigan, USA on May 24, 2013.